Evaluasi sarana dan prasarana bengkel praktik SMK teknik pemesinan di Kota Semarang berdasarkan kebutuhan kurikulum - Sudiyono Sudiyono; Moch. Alip (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2016)
Penelitian ini bertujuan untuk mengetahui: (1) kondisi sarana dan prasarana bengkel praktik SMK teknik pemesinan di Kota Semarang berdasarkan persepsi guru pengampu dan tool men, (2) tingkat kesesuaiannya terhadap standar minimal Permendiknas Nomor 40 Tahun 2008, dan (3) tingkat kecukupannya terhadap kebutuhan kurikulum. Penelitian ini merupakan penelitian evaluasi dengan model evaluasi diskrepansi. Pendekatan yang digunakan yaitu deskriptif kuantitatif dengan analisis persentase. Teknik pengumpulan data menggunakan analisis dokumen, wawancara, dan observasi. Teknik analisis yang digunakan adalah statistik deskriptif. Hasil penelitian menunjukkan bahwa: (1) Kondisi sarana dan prasarana bengkel praktik SMK Teknik Pemesinan di Kota Semarang menurut persepsi guru pengampu dan tool men pada SMK negeri ataupun swasta sudah dinyatakan layak, (2) Prasarana pada SMK negeri sesuai dengan standar minimal, sedangkan pada SMK swasta cukup sesuai, (3) Sarana pada SMK negeri sangat sesuai dengan standar minimal, sedangkan pada SMK swasta sesuai standar, (4) Prasarana pada SMK negeri cukup memenuhi kebutuhan kurikulum, sedangkan pada SMK swasta kurang memenuhi, (5) Sarana pada SMK negeri cukup memenuhi kebutuhan kurikulum, sedangkan pada SMK swasta kurang memenuhi. AN EVALUATION OF FACILITIES AND INFRASTRUCTURES OF MECHANICAL ENGINEERING VOCATIONAL SCHOOL WORKSHOP IN SEMARANG CITY BASED ON THE NEEDS OF THE CURRICULUMAbstractThis study aimed to determine: the condition of facilities and infrastructure of workshops at Mecha-nical Engineering Vocational School in Semarang City based on the perception of teachers and tool men, its relevance to the minimum standards of Education Ministry Decree No. 40 of 2008, and its leve of adequacy. This study was an evaluation study using discrepancy evaluation model. The approach used was quantitative descriptive with analysis of the percentage. The population was vocational schools in Semarang which had a Mechanical Engineering study program. The objects of study were workshop facilities in mechanical engineering, while the respondents were the teachers and the tool men of the workshop. Data were collected through analysis of documents, interviews, and observations. Data were analyzed using descriptive statistics. The results showed that: (1) The condition of the facilities at mechanical engineering vocational school workshop in Semarang according to the perceptions of teachers and tool men was adequate in public and private schools, (2) infrastructure at public schools was highly relevant to the minimum standards, while in private schools was relevant, (3) Facilities in public schools were very appropriate to the minimum standards, while in the private school they were appropriate to the standards, (4) infrastructure in public schools was sufficient to meet the needs of the curriculum, while those in the private school was not sufficient, and (5) Facilities in public schools were sufficient to meet the needs of the curriculum, while in the private schools they were insufficient.